2014
DOI: 10.3945/ajcn.113.080317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various biomarkers as potential mediators of the association between coffee consumption and incident type 2 diabetes in the EPIC-Potsdam Study , ,

Abstract: Coffee consumption was inversely associated with a diacyl-phosphatidylcholine and liver markers in both sexes and positively associated with certain acyl-alkyl-phosphatidylcholines in women. Furthermore, coffee consumption showed an inverse trend with CRP in women and with triglycerides and phenylalanine in men. However, these markers explained only to a small extent the inverse association between long-term coffee consumption and T2D risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 44 publications
9
41
2
1
Order By: Relevance
“…Several of our significant coffee‐metabolite associations were also associated with habitual coffee intake ( P < 0.05) but not always in the direction consistent with that of the current study (Table ). Conversely, population‐based metabolomic studies of habitual coffee intake have reported additional metabolites associated with habitual coffee intake (Table ) that were not amongst the 115 identified in the current study. Only four of these were analysed in the current study – serum levels of pyridoxate, a vitamin B6 cofactor, decreased with coffee intake ( P = 0.04, Q = 0.11); phenylalanine, pseudouridine and erythronate levels did not change with coffee intake ( P > 0.22).…”
Section: Discussioncontrasting
confidence: 82%
“…Several of our significant coffee‐metabolite associations were also associated with habitual coffee intake ( P < 0.05) but not always in the direction consistent with that of the current study (Table ). Conversely, population‐based metabolomic studies of habitual coffee intake have reported additional metabolites associated with habitual coffee intake (Table ) that were not amongst the 115 identified in the current study. Only four of these were analysed in the current study – serum levels of pyridoxate, a vitamin B6 cofactor, decreased with coffee intake ( P = 0.04, Q = 0.11); phenylalanine, pseudouridine and erythronate levels did not change with coffee intake ( P > 0.22).…”
Section: Discussioncontrasting
confidence: 82%
“…We also found null associations for coffee drinking and four markers (monocyte chemoattractant protein-1 (CCL2/MCP-1), IL-1β, IL-1ra, and insulin) consistent with the results from prior studies (17, 20, 21). Our null results for CRP, leptin, IL-6, serum amyloid-A (SAA) and tumor necrosis factor-α (TNF-α) are, however, consistent with some (17, 20, 21) but not all (16, 19, 20, 23) prior studies. Several observational studies have found inverse associations between coffee drinking and CRP in women (16, 1820) and men (20).…”
Section: Discussionsupporting
confidence: 79%
“…In postmenopausal women, three observational studies reported that caffeine intake was positively correlated with SHBG . Similar results were observed between coffee and SHBG in most studies among postmenopausal women, except in a small sample size study, which also included women with T2DM, potentially explaining the different conclusion . In premenopausal women, existing data are conflicting as two studies reported a positive association between coffee or caffeine consumption and SHBG levels, while two others reported no association .…”
Section: Discussionmentioning
confidence: 67%